2019
DOI: 10.1111/jcmm.14478
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl pyruvate attenuates ventilation‐induced diaphragm dysfunction through high‐mobility group box‐1 in a murine endotoxaemia model

Abstract: Mechanical ventilation (MV) can save the lives of patients with sepsis. However, MV in both animal and human studies has resulted in ventilator‐induced diaphragm dysfunction (VIDD). Sepsis may promote skeletal muscle atrophy in critically ill patients. Elevated high‐mobility group box‐1 (HMGB1) levels are associated with patients requiring long‐term MV. Ethyl pyruvate (EP) has been demonstrated to lengthen survival in patients with severe sepsis. We hypothesized that the administration of HMGB1 inhibitor EP or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, even MV with moderate tidal volumes can aggravate sepsis-induced lung injury by synergistically augmenting pulmonary cytokines, and this may play a central role in the evolution of ALI in patients with sepsis [21][22][23]. Thus, in this study, we employed our previously published animal model to simulate a clinical scenario to investigate the effects and molecular mechanisms of LMWH to attenuate VILI in endotoxemic mice [4,20]. We demonstrated that LMWH can (1) mitigate oxidative stress and improve antioxidant activity; (2) decrease inflammatory cytokines TNF-, IL-6, MIP-2 and VEGF, as well as neutrophil sequestration;…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even MV with moderate tidal volumes can aggravate sepsis-induced lung injury by synergistically augmenting pulmonary cytokines, and this may play a central role in the evolution of ALI in patients with sepsis [21][22][23]. Thus, in this study, we employed our previously published animal model to simulate a clinical scenario to investigate the effects and molecular mechanisms of LMWH to attenuate VILI in endotoxemic mice [4,20]. We demonstrated that LMWH can (1) mitigate oxidative stress and improve antioxidant activity; (2) decrease inflammatory cytokines TNF-, IL-6, MIP-2 and VEGF, as well as neutrophil sequestration;…”
Section: Discussionmentioning
confidence: 99%
“…However, even MV with moderate tidal volumes can aggravate sepsis-induced lung injury by synergistically augmenting pulmonary cytokines, and this may play a central role in the evolution of ALI in patients with sepsis [21][22][23]. Thus, in this study, we employed our previously published animal model to simulate a clinical scenario to investigate the effects and molecular mechanisms of LMWH to attenuate VILI in endotoxemic mice [4,20]. We demonstrated that LMWH can (1) mitigate oxidative stress and improve antioxidant activity; (2) decrease inflammatory cytokines TNF-α, IL-6, MIP-2 and VEGF, as well as neutrophil sequestration; (3) ameliorate lung edema and microvascular leakage; (4) attenuate caspase-3 activity and epithelial apoptosis; (5) improve gross and microscopic epithelial pathology; and (6) restore the ultrastructural integrity, Penh physiological index and functional gas exchange in a mouse model of VILI with endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of AS605240 substantially reduced damage to the diaphragmatic fibers (Figure 1F,G). Ultrasonography is a noninvasive tool for assessing the diaphragm in patients receiving MV [6,8]; therefore, to determine the effects of MV and bleomycin on diaphragm contractile function, we measured diaphragm dysfunction in the mice by using small animal ultrasound (VEVO 2100, Visual Sonics, Toronto, Canada). Relative to the VT6 group and the nonventilated control mice, the VT10 group exhibited decreased diaphragm excursion and thickening fraction (Figure 1H,I).…”
Section: As605240 Mitigated the Effects Of MV On Bleomycin-induced Viddmentioning
confidence: 99%
“…The injurious effects of MV on the ECM are triggered by increased transpulmonary pressure, heterogeneous distribution of ventilation, and increased tissue stretching and are exacerbated by limited pulmonary lymphatic drainage [1,4,5]. In addition to causing ventilator-induced lung injury, MV can result in diaphragmatic weakness and the rapid decline of diaphragm muscle contractility and endurance, a phenomenon commonly referred to as ventilator-induced diaphragm dysfunction (VIDD) [6][7][8][9]. Diaphragm muscle dysfunction can aggravate underlying respiratory insufficiency, contributing to the disability burden of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%